The Activity of Native Vacuolar Proton-ATPase in an Oscillating Electric Field – Demystifying an Apparent Effect of Music on a Biomolecule - Petrovszki, Pál; Sebők-Nagy, Krisztina; Páli, Tibor (Frontiers in Molecular Biosciences, 2021)
The effect of an oscillating electric field generated from music on yeast vacuolar proton-ATPase (V-ATPase) activity in its native environment is reported. An oscillating electric field is generated by electrodes that are immersed into a dispersion of yeast vacuolar membrane vesicles natively hosting a high concentration of active V-ATPase. The substantial difference in the ATP hydrolysing activity of V-ATPase under the most stimulating and inhibiting music is unprecedented. Since the topic, i.e. an effect of music on biomolecules, is very attractive for non-scientific, esoteric mystification, we provide a rational explanation for the observed new phenomenon. Good correlation is found between changes in the specific activity of the enzyme and the combined intensity of certain frequency bands of the Fourier spectra of the music clips. Most prominent identified frequencies are harmonically related to each other and to the estimated rotation rate of the enzyme. These results lead to the conclusion that the oscillating electric field interferes with periodic trans-membrane charge motions in the working enzyme.